2013
DOI: 10.1021/jp401283k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nucleation and Growth of Metals on TiO2: Co Compared to Au, Ni, and Pt

Abstract: The nucleation and growth of Co clusters on vacuum-annealed (reduced) and oxidized TiO 2 (110) have been studied by scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and density function theory (DFT) calculations. On vacuum-annealed TiO 2 (110), the Co clusters grow as three-dimensional islands at coverages between 0.02 and 0.25 ML, but the cluster heights range from ∼3 to 5 Å, indicating that the clusters are less than three layers high. In addition to the small cluster sizes, the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 118 publications
8
88
0
Order By: Relevance
“…At the same time Galhenage et al reported a larger diffusion coefficient on the reduced TiO 2 surface than that on non-reduced one. 46 They measured a size distribution of the metal clusters formed on vacuum-annealed (reduced) and defect-free TiO 2 (110) surface. On the reduced TiO 2 surface, they found a decrease of the number of clusters and an increased averaged-size of the clusters than on a defect-free TiO 2 surface, which suggests the enhanced diffusion on reduced TiO 2 (110) surface.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time Galhenage et al reported a larger diffusion coefficient on the reduced TiO 2 surface than that on non-reduced one. 46 They measured a size distribution of the metal clusters formed on vacuum-annealed (reduced) and defect-free TiO 2 (110) surface. On the reduced TiO 2 surface, they found a decrease of the number of clusters and an increased averaged-size of the clusters than on a defect-free TiO 2 surface, which suggests the enhanced diffusion on reduced TiO 2 (110) surface.…”
Section: Resultsmentioning
confidence: 99%
“…29(C)). These two changes can be attributed to the formation of oxides [285,287] and the agglomeration/encapsulation of clusters [288][289][290]. When the sample was treated further in H 2 atmosphere at 600 K for 60 min a small intensity Co 2p 3/2 peak appeared at 779.6 eV indicating the tendency for the reduction of Co species (Fig.…”
Section: Formation and Stabilization Of Comentioning
confidence: 99%
“…However, when the cluster is anistropic (interfacial energy depends on direction), the shape of the crystal at equilibrium is determined by Wulff construction based on evaluating surface tension as a function of interface orientation [18]. Furthermore, Galhenage et al [19] discussed the relevance of metal cluster growth behaviour on their thermodynamical properties. It was pointed out that, with decreasing metal-oxygen bond strength, the diffusion rates of metal increase, which causes larger agglomerated clusters away from the target thin film growth.…”
Section: Motivation and Backgroundmentioning
confidence: 99%